IMAGINATION AND AMBITION OF CHILDREN CHARACTER IN J.K. ROWLING NOVEL HARRY POTTER AND THE ORDER OF PHOENIX (2003) - Rahmah Nurul Aziz; Yuyun Nurulaen; Pepen Priyawan (CALL, 2020)
Every parent has high hopes for their children. They will protect their children from a bad environment to keep them from behaving badly too. This is also because their minds will be influenced by the environment in which they grow and develop. Because this research is based on literature, the researcher uses literary devices to support good and accurate research. Therefore, this paper uses qualitative research that provides description of the phenomena. For more technical analysis on the comparison of the data taken from the novel, this research uses comparative literature method. The results show that novel Harry Potter and The Order of Phoenix presents clearly the struggle of Harry and his friends to defeat Voldemort and his followers. Therefore, after the death of his parents, Harry was entrusted to a good family and an environment filled with people who really care about him. Imagination and ambition will be created on the basis of the thoughts of the doer. Therefore, the development of character in terms of ambition and imagination was found in the novel.Keywords: Literature, Children Character, Imagination, Ambition